Patient Satisfaction with Inpatient Hospital Nursing Care - Erlin Kurnia; Srinalesti Mahanani (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Patient satisfaction is the result of a patient's assessment of health services by comparing what is expected whether or not it is appropriate or not with the health services received in a hospital health setting. This study aims to describe patient satisfaction with Inpatient Installation in Simpang Lima Gumul Public Hospital of Kediri. The research design used in this study is explorative. The population in this study were all patient in Punai and Kasuari Ward at Inpatient Installation in Simpang Lima Gumul Public Hospital of Kediri. Sample method is a total sampling technique. Data collected using questionnaire. Data analysis using frequency distribution. The results patient satisfaction on the tangibles aspect was very satisfied (53.8%), on the reliability aspect was satisfied (51.9%), on the responsiveness aspect was very satisfied (48.0%) and on the assurance aspect patients was satisfied (63.5%). Patients were very satisfied on the tangibles, responsiveness and empathy aspects, while on the reliability and assurance aspects they were satisfied.